Farmer Innovations Improving the System of Rice Intensification (SRI) - Norman Uphoff (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
The System of Rice Intensification (SRI), assembled in Madagascar over a 20-year period and gaining applicationinternationally since 2000, enables farmers to raise their irrigated rice production substantially just by making changes in theway they manage their plants, soil, water and nutrients, rather than by increasing inputs such as fertilizer, water oragrochemicals. Getting more output with less cost enhances profitability. This result is quite unprecedented, as discussed inpaper accompanying this one. SRI is not considered by its proponents as a technology; and by not presenting it to farmers asa set technology, this opens SRI up to many adaptations and innovations by farmer-users, who often but not always arecollaborating with NGO or government staff in a collaborative manner. This paper reports on a number of the innovations thathave been made in SRI practices, demonstrating bothfarmer capabilities and the advantages of engagingfarmers as partnersin an ongoing process of participatory development. The companion paper which considers SRI as a system for innovationoffers a more 'macro' view of SRI spread that complements this more 'micro' perspective.